Clinical and psychopathological features of depressions with panic attacks - N. N. Ivanets; K. M. Tartynsky; G. L. Krenkel; S. V. Prokhorova (Неврология, нейропсихиатрия, психосоматика)
Objective: to study the clinical and psychopathological features of depressions with panic attacks.Patients and methods. A total of 100 in- and outpatients aged 18 to 60 years, who had been treated in the S.S. Korsakov Clinic of Psychiatry for mild and moderate depression with panic attacks, were clinically examined using the psychometric scales: the Montgomery–Asberg Depression Rating Scale, the Atypical Depression Diagnostic Scale, and the Sheehan Clinical Anxiety Rating Scale.Results. The clinical and psychopathological picture of depression with panic attacks differed significantly in three identified groups of patients with neurotic depression (ND), recurrent depressive disorder (RDD), and bipolar affective disorder (BAD). NDs with panic attacks were characterized by insignificant short-term symptoms of dreariness, indistinct anhedonia with the maximum manifestation of personality sensitivity, and a tendency to alcohol abuse. DDRs with panic attacks were inherent in melancholic and dreary symptoms, anhedonia, classical circadian mood fluctuations, and the most marked reactivity of mood. Depressions with panic attacks within BAD were typical of apathetic manifestations, hypersomnia, hyperphagia, and alcohol craving.Conclusion. Depressions with panic attacks have psychopathological features depending on whether they develop within ND, RDR, or BAD.